A practical method for the detection of freezing of gait in patients with Parkinson’s disease - Kwon Y (Dove Medical Press, 2014)
Yuri Kwon,1 Sang Hoon Park,1 Ji-Won Kim,1 Yeji Ho,1 Hyeong-Min Jeon,1 Min-Jung Bang,1 Gu-In Jung,1 Seon-Min Lee,3 Gwang-Moon Eom,1,2 Seong-Beom Koh,3 Jeong-Whan Lee,1,2 Heung Seok Jeon41Biomedical Engineering, 2Research Institute of Biomedical Engineering, Konkuk University, Chungju, Korea; 3Department of Neurology, Korea University College of Medicine, Seoul, Korea; 4Department of Computer Engineering, Konkuk University, Chungju, KoreaPurpose: Freezing of gait (FOG), increasing the fall risk and limiting the quality of life, is common at the advanced stage of Parkinson’s disease, typically in old ages. A simple and unobtrusive FOG detection system with a small calculation load would make a fast presentation of on-demand cueing possible. The purpose of this study was to find a practical FOG detection system.Patients and methods: A sole-mounted sensor system was developed for an unobtrusive measurement of acceleration during gait. Twenty patients with Parkinson’s disease participated in this study. A simple and fast time-domain method for the FOG detection was suggested and compared with the conventional frequency-domain method. The parameters used in the FOG detection were optimized for each patient.Results: The calculation load was 1,154 times less in the time-domain method than the conventional method, and the FOG detection performance was comparable between the two domains (P=0.79) and depended on the window length (P<0.01) and dimension of sensor information (P=0.03). Conclusion: A minimally constraining sole-mounted sensor system was developed, and the suggested time-domain method showed comparable FOG detection performance to that of the conventional frequency-domain method. Three-dimensional sensor information and 3–4-second window length were desirable. The suggested system is expected to have more practical clinical applications.Keywords: Parkinson’s disease, freezing of gait, acceleration, detection system, time-domain, frequency-domain